Character Customization With Cosmetic Microtransactions in Games: Subjective Experience and Objective Performance - Böffel, Christian; Würger, Sophie; Müsseler, Jochen; Schlittmeier, Sabine J. (Frontiers in Psychology, 2022)
Free games that are monetized by selling virtual items, such as cosmetic microtransactions for one’s avatar, seem to offer a better gaming experience to paying players. To experimentally explore this phenomenon, the effects of character customization with cosmetic microtransactions on objective and self-estimated player performance, subjective identification with the avatar, fun and the players' perceived competence were examined in the game League of Legends. This study introduces a new laboratory-based, experimental task to objectively measure within-game player performance. Each participant performed this game-based task in two different conditions: With a character that was customized using a provided set of cosmetic microtransactions and with a default character. Results showed that customization increased subjective identification with the player character. However, objective performance measures were unaffected by this manipulation although the novel experimental approach provided reliable performance results. Additionally, identification was positively related to perceived competence, fun, and self-estimated performance. Implications for the design of cosmetic microtransactions and their influence on competitive gaming are discussed.